The transcriptomic (RNA-Sequencing) datasets collected in the course of floral induction in Chenopodium ficifolium 459 - Gutierrez-Larruscain, David; Krüger, Manuela; Abeyawardana, Oushadee A J; Belz, Claudia; Dobrev, Petre I; Vaňková, Radomíra; Eliášová, Kateřina; Vondráková, Zuzana; Juříček, Miloslav; Štorchová, Helena (Data in brief, 2022)
The transition from vegetative growth to reproduction is the essential commitment in plant life. It is triggered by environmental cues (day length, temperature, nutrients) and regulated by the very complex signaling gene network and by phytohormones. The control of flowering is well understood in Arabidopsis thaliana and in some crops, much less is known about the other angiosperms. We performed the detailed transcriptomic survey of the course of floral induction in seedlings of Chenopodium ficifolium accession 459, a close relative of the important crop Chenopodium quinoa. It flowers earlier under short days (6 hours light) than under long days (18 hours light). Plants were sampled at the age 14, 18, 21 and 24 days in the morning and afternoon, both at long and short day, for RNA-Sequencing, and also for phytohormone analyses. We employed Illumina NovaSeq6000 platform to generate raw reads, which were cleaned and mapped against the de novo constructed transcriptome of C. ficifolium. The global gene expression levels between long and short days were pairwise compared at each time points. We identified differentially expressed genes associated with floral induction in C. ficifolium 459. Particular attention was paid to the genes responsible for phytohormone metabolism and signaling. The datasets produced by this project contributed to better understanding of the regulation of growth and development in the genus Chenopodium.
Keywords: Photoperiod; Flowering; Phytohormones; Oxidative stress; Gene expression